Системна модернізація механізмів реалізації регіональної екологічної політики - Алимов, О.М.; Драган, І.В. (Економіка природокористування і охорони довкілля, 2015)
Зосереджено увагу на питаннях модернізації механізмів реалізації регіональної екологічної політики на засадах локальної екологічної демократії з метою подолання тенденції виснаження природно-ресурсного потенціалу територій. Доведено, що зазначений процес має базуватися на принципі раціонального та збалансованого поєднання державних і ринкових, адміністративних і економічних механізмів та важелів регулювання екологічних відносин, природокористування й природоохоронної діяльності на регіональному рівні. The article focuses on issues concerning modernization of regional mechanisms for implementing environmental policies that are implemented on the basis of local environmental democracy to overcome the tendency depletion of natural resources potential areas. Determined that the current economic mechanism has a number of shortcomings and unresolved issues, and therefore the question of its improvement is extremely important. One of the main strategic objectives of this improvement, in addition to the operational tasks of economic adjustment mechanism of nature has become, in our opinion, identifying key areas of Policy reform and implementation of measures as part of the Strategy for Sustainable Development of Ukraine, now operates in Ukraine. It is proved that the modernization of mechanisms for implementing regional environmental policy in the direction of democratization should be based on rational and balanced combination of state and market, administrative and economic mechanisms and levers of regulation of environmental relations, environmental management and environmental activities at the regional level. One of the most effective mechanisms responsible above principle in conditions of limited material and financial resources are targeted environmental programs. The said mechanism, like most others in the field of environmental management is complex and operates on the basis of administrative cooperation, economic and organizational levers.